For this case we have the following expression:
![(\sqrt {12} +6) (- \sqrt {8} - \sqrt {2})](https://tex.z-dn.net/?f=%28%5Csqrt%20%7B12%7D%20%2B6%29%20%28-%20%5Csqrt%20%7B8%7D%20-%20%5Csqrt%20%7B2%7D%29)
We apply distributive property:
![(\sqrt {12} * - \sqrt {8}) + (\sqrt {12} * - \sqrt {2}) + (6 * - \sqrt {8}) + (6 * - \sqrt {2} ) =\\- \sqrt {96} - \sqrt {24} -6 \sqrt {8} -6 \sqrt {2} =](https://tex.z-dn.net/?f=%28%5Csqrt%20%7B12%7D%20%2A%20-%20%5Csqrt%20%7B8%7D%29%20%2B%20%28%5Csqrt%20%7B12%7D%20%2A%20-%20%5Csqrt%20%7B2%7D%29%20%2B%20%286%20%2A%20-%20%5Csqrt%20%7B8%7D%29%20%2B%20%286%20%2A%20-%20%5Csqrt%20%7B2%7D%20%29%20%3D%5C%5C-%20%5Csqrt%20%7B96%7D%20-%20%5Csqrt%20%7B24%7D%20-6%20%5Csqrt%20%7B8%7D%20-6%20%5Csqrt%20%7B2%7D%20%3D)
We rewrite in equivalent form:
![- \sqrt {4 ^ 2 * 6} - \sqrt {2 ^ 2 * 6} -6 \sqrt {2 ^ 2 * 2} -6 \sqrt {2} =\\-4 \sqrt {6} -2 \sqrt {6} -6 * 2 \sqrt {2} -6 \sqrt {2} =](https://tex.z-dn.net/?f=-%20%5Csqrt%20%7B4%20%5E%202%20%2A%206%7D%20-%20%5Csqrt%20%7B2%20%5E%202%20%2A%206%7D%20-6%20%5Csqrt%20%7B2%20%5E%202%20%2A%202%7D%20-6%20%5Csqrt%20%7B2%7D%20%3D%5C%5C-4%20%5Csqrt%20%7B6%7D%20-2%20%5Csqrt%20%7B6%7D%20-6%20%2A%202%20%5Csqrt%20%7B2%7D%20-6%20%5Csqrt%20%7B2%7D%20%3D)
![-4 \sqrt {6} -2 \sqrt {6} -12 \sqrt {2} -6 \sqrt {2} =\\-6 \sqrt {6} -18 \sqrt {2}](https://tex.z-dn.net/?f=-4%20%5Csqrt%20%7B6%7D%20-2%20%5Csqrt%20%7B6%7D%20-12%20%5Csqrt%20%7B2%7D%20-6%20%5Csqrt%20%7B2%7D%20%3D%5C%5C-6%20%5Csqrt%20%7B6%7D%20-18%20%5Csqrt%20%7B2%7D)
Answer:
![-6 \sqrt {6} -18 \sqrt {2}](https://tex.z-dn.net/?f=-6%20%5Csqrt%20%7B6%7D%20-18%20%5Csqrt%20%7B2%7D)
Answer:
Step-by-step explanation:
(0, -3) not a solution
(2,1) solution
(3,-4) not a solution
(-5,7) solution
Answer:
c) three
-----------------------------------------------------------------------------------------------------------------
Step-by-step:
The tetrahedron is a triangular pyramid with equilateral triangles on each face.
Answer:
115ft^2
Step-by-step explanation:
10 * 11.5 = 115
Step-by-step explanation:
By Factor Theorem, (x + 3) is a factor of H(x) if and only if H(-3) = 0.
3(-3)³ - 2(-3)² + (-3)k - 3 = 0
-81 - 18 - 3k - 3 = 0
3k = -102
k = -34.